2016
DOI: 10.1007/s00330-016-4241-6
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion MR imaging for breast lesions: comparison and correlation with pharmacokinetic evaluation from dynamic contrast-enhanced MR imaging

Abstract: • IVIM provided diffusion as well as perfusion information • IVIM could help differential diagnosis of breast lesions • Correlations were found between perfusion-related parameters from IVIM and DCE MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
69
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 36 publications
12
69
3
Order By: Relevance
“…In the present study, the f value did not differ significantly between the MIBC and NMIBC groups, which was similar to other findings . f was sensitive to the maximal b value employed and their potential sampling from non‐Gaussian effects . A previous study found that the f value was significantly increased in tumors with maximal b value below 750 s/mm 2 in prostate cancers and decreased or indistinguishable from normal tissues with higher maximal b value .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the f value did not differ significantly between the MIBC and NMIBC groups, which was similar to other findings . f was sensitive to the maximal b value employed and their potential sampling from non‐Gaussian effects . A previous study found that the f value was significantly increased in tumors with maximal b value below 750 s/mm 2 in prostate cancers and decreased or indistinguishable from normal tissues with higher maximal b value .…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the D* values in the MIBC group were not significantly lower than the D* values in the NMIBC group. Similarly, previous studies of liver or breast have reported that D* values in malignant lesions were lower than or indistinguishable from those of benign lesions . The repeatability estimates found for D* in this work were relatively good, with an ICC greater than 0.75 for D* using the biexponential model, while D* had previously been found to be less stable, with wide variability in tumors .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although it is still unclear how closely the f value relates to delayed persistent proportions in our study, it could be postulated by the effect of "late enhancement," which corresponds to a progressive interstitial accumulation and combines with the rapid initial slope of enhancement . Therefore, the f value seems to be influenced not only by the quantity of neovascularity, but also by the incoherent flow in small vessels . As the median f values were reported to be higher in breast cancers (9.1–11.9%) than in benign lesions (5.0–5.3%) or normal breast tissue (1.5–8.3%), it was suggested that the most aggressive breast cancers could show the highest f values .…”
Section: Discussionmentioning
confidence: 61%
“…The ADC value is a quantifiable value that provides a measurement of tissue cellularity, which is influenced not only by water diffusion but also by perfusion . The perfusion effect may result in overestimation of the ADC value owing to an increased microvessel count for tumor angiogenesis . Throughout the IVIM, the D value, which reports more precise cellularity and provides increased specificity in diagnosing breast cancer, can be acquired by avoiding microcirculation contributions .…”
Section: Discussionmentioning
confidence: 99%